Design and critical evaluation of permanent magnet wind generator technology for small-scale wind energy systems - Labuschagne, Casper Jeremias Johannes (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD) -- Stellenbosch University, 2022.